THE ROLE OF THE INTERNATIONAL ASSESSMENT SYSTEM IN SPEECH DEVELOPMENT OF PRIMARY CLASS STUDENTS (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, while talking about the requirements of the international assessment program and the principles of introduction into the educational system, the important features of the PISA, PIRLS international assessment programs are revealed based on the opinions of foreign scientists and scientific research works.